EFFECTS OF PROPOLIS POWDER ON GROWTH PERFORMANCE, PHYSIOLOGICAL TRAITS AND CARCASS CHARACTERISTICS OF BROILER CHICKENS - kairalla, majdi (Food and Feed Research, 2026)
Abstract: Assessing the effects of incorporating propolis as a natural growth enhancer of broiler chickens for growth performance, physiological traits and carcass characteristics was the aim of this study. A total of 240 one-day-old broiler chicks (Cobb 500) were individually weighed and randomly divided into four equal groups, with 60 chicks in each. Each group comprises four replicates, each containing 15 birds. Propolis powder was supplemented into broiler diets at dosages of 0, 200, 400, and 600 mg/kg diet. On day 42, two birds per replication (8 birds per treatment) were selected to evaluate blood biochemistry and carcass yield. The results showed that the group of chickens given 400 mg/kg of propolis grew better and converted feed into body weight more efficiently than the other groups. The chickens who had propolis baseline diets exhibited a significant (P < 0.05) reduction of total cholesterol, triglycerides, and LDL levels in comparison to the control group. The incorporation of 600 mg/kg propolis resulted in diminished broiler performance and carcass yield. In conclusion, propolis can be administered to broilers at a dosage of up to 400 mg/kg without detrimental effects on growth performance.